2010
DOI: 10.3923/pjbs.2010.738.742
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Catecholamine Levels and Outcome in Patients with Severe Head Trauma

Abstract: Some studies have shown that catecholamines and the changes in their levels during and after head trauma can be useful in predicting the outcome in head trauma patients. The goal of this study is to search for a probable relation between urine levels of catecholamines and prognosis in patients with severe head trauma. Fifty four patients with severe head trauma Glasgow Coma Scale (GCS < or = 8) on admission time were recruited in Imam Reza Hospital within one. These patients were included when having no major … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 9 publications
0
3
0
2
Order By: Relevance
“…The stimulating effect of pain and various other stress factors on the sympathetic nervous system resulted in persistently high plasma noradrenaline levels in critically injured patients. Pain is considered a powerful provoker of the sympathoadrenal axis, which increases sympathetic tone and catecholamine release [58]. In this study, significantly higher noradrenaline levels were observed in cattle slaughtered using a commercial sharp knife, which is believed to induce more stress and pain in the animals compared to those slaughtered with a sharp knife.…”
Section: Influence Of Knife Sharpness On Hormonal Parametersmentioning
confidence: 55%
“…The stimulating effect of pain and various other stress factors on the sympathetic nervous system resulted in persistently high plasma noradrenaline levels in critically injured patients. Pain is considered a powerful provoker of the sympathoadrenal axis, which increases sympathetic tone and catecholamine release [58]. In this study, significantly higher noradrenaline levels were observed in cattle slaughtered using a commercial sharp knife, which is believed to induce more stress and pain in the animals compared to those slaughtered with a sharp knife.…”
Section: Influence Of Knife Sharpness On Hormonal Parametersmentioning
confidence: 55%
“…These findings are in line with similar reports. [8,9] Dumont et al [5] studied 65 patients with traumatic brain injury in a retrospective manner to determine the effect of prehospital hyperventilation on in-hospital mortality. According to their findings, survival was related to admission PCO 2 in patients requiring intubation.…”
Section: Discussionmentioning
confidence: 99%
“…Однією з важливих і актуальних проблем дитячої нейрохірургії є черепно-мозкова травма дитини першого року життя [6]. Черепно-мозкова травма дитини -це потужна стресова ситуація, яка створює передумови для розвитку порушення психоемоційного стану батьків, що, у свою чергу, негативно впливає як на стан батьків, так і на стан дитини та потребує заходів психотерапевтичної корекції [7,8].…”
Section: вступunclassified